Identification and characterization of differentially expressed miRNAs in HepG2 cells under normoxic and hypoxic conditions. Issue 29 (29th May 2019) - Kong, Fanzhi; Ran, Wei; Jiang, Ning; Li, Shize; Zhang, Dongjie; Sun, Dongbo
Abstract : MicroRNAs (miRNAs) are important post-transcriptional regulators involved in hypoxia conditions; however, their roles in HepG2 cells remain poorly understood. Abstract : MicroRNAs (miRNAs) are important post-transcriptional regulators involved in hypoxia conditions; however, their roles in HepG2 cells remain poorly understood. Our previous study showed that hypoxia treatment modulated gene expression accompanied by with HepG2 cell proliferation arrest and increased cell death. To better understand the mechanism of phenotypic changes of HepG2 under hypoxia conditions; we conducted a comparative RNA sequencing to identify differentially expressed miRNAs between hypoxia treatment and control cells. In total, 165 differentially expressed miRNAs were identified, among which the expression of 114 miRNAs were up-regulated and that of 51 miRNAs were down-regulated in hypoxia treated HepG2 cells. Expression profiles of eleven randomly selected miRNAs were validated by qRT-PCR. Furthermore, 19 367 annotated target genes of differentially expressed miRNAs were predicted by bioinformatics tools. The Gene Ontology analysis indicated that the molecular function of target genes was primarily related to binding and catalytic activity, and that the Kyoto Encyclopedia of Genes and Genomes annotation for target genes were further classified into pathways involved in cellular processes, metabolism, organismal systems, genetic information processing, human disease and environmental information processing. Among the environmental information processing, certain pathways associated with cell proliferation and apoptosis, such as the hippo signalling pathway, wnt signalling pathway, MAPK signalling pathway and Jak-STAT signaling pathways, represented potential factors in the response to hypoxia treatment. In conclusion, the expression profiles of miRNA in HepG2 cells were significantly altered under hypoxia conditions; which were closely related to cell proliferation arrest and apoptosis. Our findings expand our understanding of miRNAs function in regulating cell fate under hypoxia conditions.